Impact of Government Expenditure on Poverty Rate Reduction in East Java Province - Dya Ayu Fitaloka Candra Kartika; Sebastiana Viphindrartin; Herman Cahyo Diartho (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
East Java is a province with a number of poor people, but on the other hand, both nationally and province, there is a reduction in poverty and inequality. This study aims to examine the effect of government expenditures on reducing poverty through economic growth and increasing the Human Development Index (HDI) in East Java Province 2015-2019. This research uses explanatory research type. Research variables include independent variables in the form of government expenditure, intervening variables namely economic growth and HDI or Human Development Index, and the dependent variable, namely poverty. Data analysis was performed using path analysis. The test results show that government Expenditure (GEXP) has no effect on Economic Growth (EG). Government Expenditure (GEXP) has no effect on the Human Development Index (HDI). Government Expenditure (GEXP) has no effect on Poverty (P). Economic Growth (EG) has no effect on poverty (P). The Human Development Index (HDI) has a significant effect on Poverty (P). Based on these results, it can be concluded that poverty alleviation can be achieved if there is an increase in the quality of human resources as reflected in the HDI.